Measuring the effect of the misery index on international tourist departures: Empirical evidence from Mexico - Fernando Sánchez López (Economies, 2022)
Tourism's capacity to alleviate poverty is one of the most important subjects in tourism studies, as tourism is capable of boosting economic growth and generating employment. On the other hand, it is known that lack of income and unemployment have negative effects on outbound tourism; however, the relationship between outbound tourism and poverty has been understudied. In this paper, we compute a vector autoregressive (VAR) model to analyze the relationship between tourist departures from Mexico and a modified misery index to measure the effect of the loss of well-being, measured in terms of this index, on the number of outbound tourists. The results indicate that increases in the misery index have negative effects on the number of outbound tourists. Conversely, there is no statistically significant effect of tourist departures on the misery index. The results also suggest that the depreciation of the national currency exerts a positive effect on the misery index. Finally, based on the historical decomposition analysis, it was verified that the misery index was not closely related to outbound tourism during the first COVID-19 wave.
Keywords: 330; international tourism; Okun's misery index; outbound tourism; poverty; unrestricted VAR